KONTRADIKSI PENAFSIRAN IMAM JALALAIN: ANALISA PERBANDINGAN PENAFSIRAN IMAM JALALUDDIN AL-MAHALLI DAN JALUDDIN AL-SUYUTHI DALAM TAFSIR AL-JALALAIN - Rifqatul Husna; Putri Azizah Annuriyah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
This article examines several different interpretations of Tafsir Jalalain's, namely those of Jalaluddin Al-Mahalli and Jalaluddin Al-Suyuthi. In collaborating on his work, the two are not in the same era but different generations, but the interpretation of both is almost the same. The purpose of this research is to find out the different interpretations of each commentator based on the social and intellectual life of both. The method used is library research with Tafsir Jalalain as the primary source. By looking directly at the results of interpretation from various points of view, the results obtained include that Jalaluddin Al-Mahalli's method of interpretation is mainly sourced from narrations (al-ma'thur). At the same time, Jalaluddin As-Suyuthi is the other way around, namely by reason (al-ra'yu). Also, in addressing the various qiraah, the two are different. Al-Mahalli, in his qira'ah interpretation, does not change the original meaning at all, but in Al-Suyuthi, the various Qiraat presented can change the meaning of interpretation between one Qiraat and another. In terms of Al-Mahalli's theology, his interpretation refers to the teachings of the Ash'ariyah school. At the same time, Al-Suyuthi belongs to the Ash'ariyah school, but in his interpretation, he does not refer to Ash'ariyah